The deductibility of damages and associated legal expenses for the purposes of determining taxable income in South Africa - Madovi, Ezekiel (Rhodes University, Faculty of Commerce, Department of Accounting, 2017)
The deduction of damages and the associated legal costs must satisfy the requirements of the preamble to section 11 and section 11(a) of the Income Tax Act 58 of 1962, read with section 23(g) (referred to as the general deduction formula). This research examined under what circumstances a payer of damages and the associated legal costs would be able to claim a deduction from taxable income. This research also considered whether or not the issue of fault is a relevant consideration in determining whether a deduction should be allowed. In some cases the courts appear to have disallowed a deduction if the expenditure or loss was incurred as a result of a negligent or unlawful act. In other instances the courts have allowed the deduction of damages despite the expenditure or loss having been incurred as a result of a negligent or unlawful act. The research concludes that negligence is not a relevant consideration in the deduction of damages and the associated legal costs. In order to secure a claim for damages the taxpayer must prove that the expenditure was incurred in the production of income and it was expended for the purposes of trade. Associated legal costs are only deductible if the damages satisfy the requirements of section 11(c).
Keywords: Income tax -- Law and legislation -- South Africa; Damages -- Taxation -- South Africa; South Africa. Income Tax Act, 1962